Impact of Socio-demographic Factors on the Cognitive Well-being of Children with Special Needs in Low-and Middle- Income Countries: A Case of Morocco - Descriptive and Multilevel Approaches - Loudghiri, Khadija; Houmine, Mohammed (Department of Public Administration, 2024)
Using data from the 2014 General Census of Population and Housing in Morocco as an example, this paper aims to examine the socio-demographic barriers that hinder the education and literacy of children with special needs (CWSN) in low-and middle-income countries (LMICs). A combined descriptive analysis and mixed effects logistic regression was used to analyse these data. Comparative findings from international studies on this topic on CWSN in LMICs were also used. The above data provide information on the demographic, socio-economic, cultural and environmental characteristics of a representative sample of 10% of the Moroccan population and households. Both individual and contextual information on people with special needs was collected, including educational status, literacy and socio-demographic characteristics. The rate of school exclusion for CWSN is significantly higher at 0.485 compared to 0.146 for children without special needs. In addition, 34% of CWSN aged 10-17 are not literate. The likelihood of enrolment and literacy for these children is influenced by several socio-demographic factors. Moroccan CWSN have limited access to opportunities for cognitive well-being. It is therefore crucial that policymakers prioritise the cognitive well-being of these children, which is a fundamental right rather than a privilege.